Highly Reproducible Fabrication of Perovskite Films with an Ultrawide Antisolvent Dripping Window for Large‐Scale Flexible Solar Cells. Issue 1 (4th December 2020) - Kong, Xiangyu; Jiang, Yue; Li, Zhuoxi; Zhou, Youshuang; Xu, Zhengjie; Cong, Chen; Gao, Xingsen; Lu, Xubing; Zhou, Guofu; Liu, Jun-Ming; Kempa, Krzysztof; Gao, Jinwei
Abstract : Although perovskite solar cells (PSCs) have exhibited a high‐power conversion efficiency, the reproducibility of high‐quality perovskite films is still a big challenge for large‐scale flexible devices. One reason is the super narrow antisolvent dripping window, the other one is the difficulty in controlling the secondary phases. Herein, 18C6 is introduced into the perovskite precursor to achieve a high‐quality and reproducible large‐scale (7 × 7 cm 2 ) flexible perovskite film by enlarging the antisolvent dripping window from 2 to 20 s, with an average efficiency of 13.33% (best 15.80%). Moreover, from the in situ grazing‐incidence wide‐angle X‐ray scattering result, the 2H phase perovskite is highly suppressed with the additive of 18C6. The generality of the approach is also demonstrated in other antisolvents such as ethyl acetate. This finding provides an innovative solution to the realization of repeatable, large‐scale solution fabrication of PSCs. Abstract : A small molecule of 18C6 is introduced into the perovskite precursor for elongating the antisolvent dripping window from 2 to 20 s, achieving a high‐quality and reproducible perovskite film.